POLA KOMUNIKASI INTERPERSONAL PADA GENERASI Z DALAM MEMBENTUK KONSEP DIRI YANG POSITIF - Saraswati, Prihatin (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2024)
The purpose of this study is to find out the interpersonal communication patterns of Generation Z in forming a positive self-concept—types of descriptive qualitative research. Meanwhile, the subset was determined using a sample of 3 informants as students. The sample drawing technique uses purposive sampling—data collection techniques using observation, in-depth interviews and documentation. The data analysis method uses a descriptive method that will describe, describe and explain the interpersonal communication patterns of Generation Z in forming a positive self. Based on the results of the research and discussion, it was obtained that the pattern of direct face-to-face interpersonal communication is very necessary to develop oneself based on the condition of other people, who are good as figures who can provide self-comparisons so that it will become a positive self-concept. Human interaction is influenced by the factor of imitation or imitation, the factor of suggestion or acceptance of other people's opinions, the sympathy factor, which is caring for others, and the empathy factor, which is to feel the condition of others.